O extrato hidroalcóolico das folhas de Arachis hypogaea L (Fabaceae) produz atividade antioxidante e anti-inflamatória in vitro sem a indução de toxicidade in vitro ou in vivo - Cossetin, Jocelene Filippin (2020)
Arachis hypogaea (peanut) leaves are traditionally used for the treatment of insomnia and inflammation. This study aimed to examine the phytochemical composition of peanut leaf hydroalcoholic extract (PLHE) and to describe its potential toxic effects and antioxidant and anti-inflammatory properties. Qualitative chemical analysis of PLHE by high performance liquid chromatography coupled with high resolution mass spectrometry(UHPLC-ESI-HRMS) allowed the identification of eight types of metabolites (totaling 29 compounds).The 1,1-diphenyl-2-picrylhydraz (DPPH) test revealed that PLHE had significant antioxidant effects; and also exhibited nitric oxide (NO) uptake capacity. Human peripheral blood mononuclear cells (PBMCs) exposed to PLHE for 24 h showed no reduction in cell viability (MTT assay), or any significant increase in denaturation of the Double strand free DNA (Picogreen Test). PLHE reversed H2O2 induced cytotoxicity and reduced IL-1β production in human PBMC. Single-dose in vivo toxicity of PLHE (2000 mg/kg) was evaluated in female Wistar rats for 14 days, and repeated dose toxicity assessment (100, 300 or 1000 mg/kg) was performed in female and male Wistar rats for 28 days using the guidelines of the Organization for Economic Cooperation and Development (OECD, 423 407). Single and repeated dose PLHE treatment did not cause mortality or morbidity or induced changes in behavioral, locomotion, hematological or biochemical parameters. In repeated dose toxicity of PLHE, we evaluated organ weights and only males showed reduction in relative liver weight (100 mg/kg) and increase in total kidney weight (1000 mg/kg). In addition, locomotor activity (open field test), motor coordination (rotarod test) and anxiety behavior (elevated plus-maze) were investigated and no alteration or damage was found in any of these factors. Oxidative stress and DNA damage were also evaluated after repeated dose treatment. Only the doses of 100 and 1000 mg/kg (females) or 1000 mg/kg (males) showed a reduction in the levels of dsDNA in the liver, or the dose of 300 mg/kg (males) caused a decrease in the levels of dsDNA in the kidney. PLHE treatment (1000 mg/kg, female) significantly increased total liver thiols. Thus, PLHE may be a source of bioactive compounds and has antioxidant and anti-inflammatory properties without cytotoxicity or genotoxicity in human PBMCs or single or repeated dose toxicity in rats.